(untitled) (Journal of Chemical Engineering, 2010)
Plant-wide oscillations are common in many processes. Their effects propagate to many units and may impact the overall process performance. It is important to detect and diagnose the cause of such oscillations in order to rectify the situation and maintain the proper profitability of the plant. This paper proposes a new procedure to detect and diagnose plant-wide oscillations using routine operating data. The method has been developed based on the nonlinearity information in the process data. A new Total Nonlinearity Index (TNLI) has been defined to quantify nonlinearities. The method is based on the assumption that the nonlinearity is highest near the source and decreases as one moves away from the source. This assumption is true because chemical processes have the nature of low-pass filters and they filter out gradually higher order harmonics of the signals. Signals with higher order harmonics are generally more nonlinear. The proposed diagnostic method has already been successfully applied for troubleshooting many industrial plant-wide oscillation problems. Two of such case studies have been presented in this paper. Journal of Chemical Engineering Vol.ChE 24 2006 50-60